AB0150 Regulation of SOCS1, SOCS2 and SOCS3 expression in patients with early arthritis. (23rd January 2014) - Ortiz, A.M.; Villares, R.; Lamana, A.; Costas, C.; Lόpez-Santalla, M.; Mellado, M.; González-Άlvaro, I.
Abstract : Background: Most cytokines involved in the pathogenesis of rheumatoid arthritis (RA) act through receptors that trigger distinct signalling pathways that are initiated through activation of the JAK/STAT system which up-regulates the expression of several genes, including those related to suppressors of cytokine signalling (SOCS). SOCS1 and SOCS3-deficient mice show severe joint inflammation. By contrast, SOCS3 overexpression alters T-cell response and prevents the development of collagen-induced arthritis. Studies on SOCS expression in patients with RA are limited and contradictory. Objectives: To study the expression of SOCS1, SOCS2 and SOCS3 during the follow-up of patients with early arthritis (EA). Methods: We have analyzed data from 190 patients from our prospective EA register (82% women, median age 53.6 years). Demographic, disease-related and prescribed treatment variables, as well as peripheral blood samples, were collected at each visit (baseline, 6, 12, 24 and 60 months) according to the protocol. Levels of SOCS1, SOCS2 and SOCS3 expression and β-actin as housekeeping gene were measured using quantitative real-time PCR (qRT-PCR) in 327 mRNA samples obtained from peripheral blood mononuclear cells. qRT-PCR data were normalized against β-actin expression and 2 -ΔΔCt were calculated against the mean expression of SOCS genes in 17 healthy volunteers (53% female, 42.5 years). For 68 patients, we have collected two to four samples, including the baseline visit (184 samples). In order to determine the effect of the independent variables on levels of SOCS expression, a generalized linear model, nested by patient and visit, was fitted using the xtgee command of Stata 10.1 for Windows (StataCorp LP, College Station, TX, USA). Results: SOCS1, SOCS2 and SOCS3 expression levels were significantly lower at baseline for patients with EA than for healthy controls (median 2 -ΔΔCt 0.57 [IQR: 0.27-1.2] versus 1.31 [0.96-1.64], p=0.001; 0.57 [0.34-1.1] versus 0.94 [0.78-1.66], p=0.0009 and 0.61 [0.26-1.3] versus 0.95 [0.77-1.97], p=0.01, respectively). In addition, levels of all three SOCS diminished over the follow-up According to this finding, in the multivariate analysis an increase of SOCS2 and SOCS3 levels was significantly associated to high disease activity assessed through the DAS28, whereas the increase in SOCS1 levels was significantly associated with a decrease in haemoglobin concentration and with the use of TNF blockers. Finally, elderly patients showed significantly lower levels of SOCS3. Conclusions: SOCS expression in peripheral blood mononuclear cells from patients with EA is lower than that of healthy controls, even at baseline when the expression of these molecules should theoretically be increased due to higher disease activity. This work has been supported by the RETICS Program, RD08/0075 (RIER) and FIS 080754, from Instituto de Salud Carlos III (ISCIII). Disclosure of Interest: None Declared